The potential of two types of urban flooding to cause material damages in Lisbon, Portugal - Leal, Miguel (2017)
The incapacity to cope with heavy rainfall events leads to flooding in urban areas. Urban flooding is usually divided into pluvial flooding, sewer flooding, among others. Determining which of these types was responsible to cause a flooding occurrence is, in most cases, an error-prone task, because it can be triggered by more than one of them and there is frequently an overlap in their extent. Given these problems, a classification based on the hydro-geomorphological features was applied to Lisbon, in which the relief and the ancient floodplains are still crucial factors in the city’s current overland flow behavior. Two types of flooding are proposed: flooding related to natural drainage network (FREN) and flooding unrelated to natural drainage network (FUNN). In order to determine the material damages associated to FREN and FUNN and their spatial distribution, an insurance flooding database (2000–2011) was used. Through the accurate location of the APS (the Portuguese Association of Insurers) database flooding records triggered by rainfall and the reconstruction of the Lisbon’s natural drainage network, it was possible to define which type of flooding caused each reported claim. There are different spatial patterns in Lisbon concerning FREN and FUNN. FREN occurs along the valley bottoms, while FUNN has a more scattered spatial pattern, meaning that FUNN can occur where there are overland flow difficulties. 53% of the claims were caused by FUNN; however, higher payouts are associated with FREN (58%). Resorting only to the claims recorded during an extreme rainfall event (in 18 February 2008), the weight of FREN is even more pronounced with 58% of the claims and 71% of the payouts. This proves the higher FREN’s potential to cause material damages when compared to FUNN’s. This knowledge can be applied to the flooding mitigation or adaptation measures to be included in urban planning